Determination of adequate "Overage" in the formulation of vitamin D3 capsules in dietary supplements - Dimitrijević, Zvezdana (Archives of Pharmacy, 2022)
Many manufacturers of dietary supplements formulate products so that they contain excess nutrients, the so-called “overage” compared to the declared content, in order to compensate for losses due to nutrient degradation during shelf life, and to compensate for the variability of the production process and testing methods. For vitamins overage ranges up to + 50%. In order to reduce "overage", having in mind that it is a liposoluble vitamin in a high dose, in the formulation we decided to use powdered vitamin D3 active substance, and the formulation of white hard gelatin capsules in PVC blisters. The content of vitamin D3 by HPLC was analyzed after the production of hard gelatin capsules with a declared 2000 IU (50 mcg), with an overage of 15%, as well as the content after one year of storage at room temperature (finished product warehouse with a temperature of 18-25 ° C and moisture up to 65 RH). The results of the content analysis showed that there was no high percentage of degradation after one year of storage under the stated conditions (half the shelf life of the product). Our results therefore question the need for a high percentage of "overage" for products with vitamin D3 content greater than 2000 IU within the production formula, suggesting that product stability over time can be preserved by proper excipient selection, encapsulation method, use of opaque, white gelatin capsules, even in an aluminum-PVC blister. Certainly, the content analysis should be performed after the expiration date.